Typical winter haze pollution in Zibo, an industrial city in China: Characteristics, secondary formation, and regional contribution. (October 2017) - Li, Hui; Ma, Yongliang; Duan, Fengkui; He, Kebin; Zhu, Lidan; Huang, Tao; Kimoto, Takashi; Ma, Xiaoxuan; Ma, Tao; Xu, Lili; Xu, Beiyao; Yang, Shuo; et al.
Abstract: Heavy haze pollution occurs frequently in northern China, most critically in the Beijing-Tianjin-Hebei area (BTH). Zibo, an industrial city located in Shandong province, is often listed as one of the top ten most polluted cities in China, particularly in winter. However, no studies of haze in Zibo have been conducted, which limits the understanding of the source and formation of haze pollution in this area, as well as mutual effects with the BTH area. We carried out online and continuous integrated field observation of particulate matter in winter, from 11 to 25 January 2015. SO4 2−, NO3 −, and NH4 + (SIA) and organics were the main constituents of PM2.5, contributing 59.4% and 33.6%, respectively. With the increasing severity of pollution, the contribution of SIA increased while that of organics decreased. Meteorological conditions play an important role in haze formation; high relative humidity (RH) and low wind speed increased both the accumulation of pollutants and the secondary transition from gas precursors (gas-particle phase partitioning). Since RH and the presence of O3 can indicate heterogeneous and photochemistry processes, respectively, we carried out correlation analysis and linear regression to identify their relative importance to the three main secondary species (sulfate, nitrate, and secondary organic carbon (SOC)). We found that the impact of RH is in the order of SO4 2−  > NO3 −  > SOC, while the impact of O3 is reversed, in the order of SOC > NO3 −  > SO4 2−, indicating different effect of these factors on the secondary formation of main species in winter. Cluster analysis of backward trajectories showed that, during the observation period, six directional sources of air masses were identified, and more than 90% came from highly industrialized areas, indicating that regional transport from industrialized areas aggravates the haze pollution in Zibo. Inter-regional joint prevention and control is necessary to prevent further deterioration of the air quality. Graphical abstract: Highlights: The main constituents of PM2.5 were SNA (53.02%) and organic matters (29.97%). Sulfate and nitrate increased continually along the evolution of pollution. The influence of the RH on the secondary formation was in the order of SO4 2−  > NO3 −  > SOC. The regional impact was significant, inter-regional joint prevention is necessary for the government. Abstract : Sulfate and nitrate increased with the evolution of winter haze in Zibo city, which was influenced strongly by the relative humidity, implying a heterogeneous process in this area.